Optimization of culture conditions for production of L-glutaminase enzyme from Klebsiella pneumoniae - Ibrahim, Asmaa E.M.; Elariny, Eman. Y.T.; Abdel-Hafez, Lina J.M. (Journal of Advanced Veterinary Research, 2024)
The main objective of this study was to investigate the production and activity of glutaminase by some clinical bacterial species. Two marine specimens, saltwater and sediment gathered from the Red Sea coast of Hurghada, Egypt, yielded 100 marine bacterial isolates altogether. Based on cultural and biochemical testes, there were 60 isolates of Gram-negative bacteria belong to the Escherichia coli, including 10, isolates of Pseudomonas aeruginosa, 25 isolates of Klebsiella pneumonia (K. pneumonia) and 2 Acinetobacter junii. Whereas the remaining isolates were identified as Gram-positive bacteria were distributed as 3 Enterococcus faecalis. All the bacterial isolates were screened for L-glutaminase enzyme activity using rapid plate assay. The isolate showing the highest production of L-glutaminase was identified by 16S rDNA gene sequence analysis. Then L-glutaminase production was optimized by various process parameters such as: The effect of incorporation of additional carbon source, nitrogen source, different concentrations of sodium chloride (0.2-1.2 %), initial pH values (4-9), incubation temperatures (25-50oC), and incubation periods (24-120 h.). Fifty isolates were found to be L-glutaminase producers. The zone index was calculated for all L-glutaminase producing samples which are ranged from 5.0 to 1.0. The maximum zone index was given by K. pneumonia. The enzymatic activity was ranged from (82.75±4.71-15.7±0.86) IU/ml. The maximum activity was recorded by K. pneumonia. Various parameters that enhance the yield of L-glutaminase by K. pneumonia was investigated and resulted in fructose was the best carbon source, beef extract was the best nitrogen source, 1% of NaCl concentration was the optimum for L-glutaminase production from K. pneumonia, the optimum L-glutaminase production was recorded at pH 8.0, The maximum enzyme productivity was obtained at 96 h., Maximum L-glutaminase production was noticed at a temperature of 40°C. In Conclusion, the current study showed microbial source of glutaminase enzyme production from K. pneumonia pure culture. Nutritional parameters, such as carbon and nitrogen sources also played an important role in enhancing the yield.